A scoping review considering potential biomarkers or functional measures of gastrointestinal dysfunction and enteral feeding intolerance in critically ill adults. (December 2022) - Jenkins, Bethan; Calder, Philip C.; Marino, Luise V.
Summary: Background & aim: Enteral feeding intolerance (EFI) as a result of gastrointestinal (GI) dysfunction in critically ill adults can lead to suboptimal nutritional delivery, increasing the risk of hospital acquired malnutrition. There are no validated measures of EFI or consensus as to which measures could be used to define EFI. The aim of this scoping review is to explore the validity of biomarkers, physiological or functional measures of GI dysfunction and EFI in critically ill adults characterising their use in routine clinical practice to identify those with GI dysfunction to better guide nutritional support. Methods: Database searches were completed in Ovid MEDLINE, Embase, CINAHL and Web of Science using the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines. The search was performed until June 2022. Articles were included if they reported original studies that identify potential biomarkers or functional measures of EFI in critically ill adults. A nine-stage process was completed to extract and complete data synthesis. Results: 139 unique articles were identified. Following review of titles and abstracts, 114 of these articles were excluded, three further articles were excluded after full text review and 22 articles met the inclusion criteria. A thematic analysis of the articles included identified three overarching themes of GI dysfunction: (1) Serum biomarkers, (2) Physiological markers, and (3) Functional markers. Within the category of serum biomarkers, a further three sub-categories were identified: (i) enterohormones, (ii) markers of enterocyte function, and iii) cytokines and neurotransmitters. Some associations were seen between EFI and heparin binding protein, intra-abdominal pressure, cholecystokinin and acetylcholine levels but no markers are currently suitable for daily clinical use. Conclusions: Further larger studies are required to characterise the relationships between serum biomarkers, physiological and functional makers of GI dysfunction in critically ill adults. A robust definition of GI dysfunction should be included in any future research.